A new high-yield rice for irrigated ecology (FOFIFA 190) in Madagascar - CGIAR Research Program on Rice (2020)
Breeder seeds and Foundation seeds were delivered to the National Research Institute (FOFIFA) and the local seed producer cooperatives. Consequently the seed producer associations produced certified seeds.